EFFECT OF WORK-LIFE BALANCE AND EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE: (Study on Employees of PT Bank Tabungan Negara Medan Branch Office Consumer Collection Recovery and Asset Sales Unit Division) - Matakena, Selli; Mardhiyah, Ainun; Siregar, Onan Marakali (Transpublika Publisher, 2024)
This study examines the influence of work-life balance and emotional intelligence on employee performance within PT State Savings Bank's Medan Branch Office Consumer Collection Recovery and Asset Sales Unit Division, employing a quantitative research approach. The 61 employees in this division serve as the study's population, selected using a nonprobability sampling technique with a saturated sample model. Data collection involves primary methods like observation, interviews, and questionnaires, supplemented by secondary data gathered through library research. Through a series of analytical procedures, including validity and reliability tests, classic assumption tests, multiple linear analysis, and hypothesis testing, the research reveals that both work-life balance and emotional intelligence have significant individual effects on employee performance. Furthermore, when considered collectively, these variables exhibit a substantial influence on employee performance, as indicated by an R value of 0.885 or 88.5%. The adjusted R Square value shows that work-life balance and emotional intelligence can account for 77.6% of the variance in employee performance, while the remaining 22.4% is influenced by unexamined factors.